A case of medical liability involving an unexpected systemic amyloidosis. (May 2022) - Galante, Nicola; Ciprandi, Barbara; Franceschetti, Lorenzo; Leone, Biagio Eugenio; Riva, Stefania; Gentilomo, Andrea
Highlights: Autopsy is fundamental to evaluate cases related to alleged medical claims. Biventricular hypertrophy with normal blood pressure may suggest an amyloid cardiomyopathy. AL (light chains) amyloidosis is the most common type of systemic amyloidosis. Congo Red staining shows a yellow-green birefringence of amyloid under polarized light. Immunohistochemistry identifies the amyloid deposits and the amyloid precursors. Abstract: The authors present a case of fatal amyloid cardiomyopathy, which was diagnosed only upon autopsy. A 57-year-old man was admitted to the hospital for scheduled percutaneous cardiac procedure of transcatheter radiofrequency ablation due to persistent atrial fibrillation and atrial flutter. Ventricular fibrillation was recorded in the monitor 2 h after the surgical procedure. Therefore, he was defibrillated and intubated, but he died for nosocomial pneumonia 26 days after being admitted. A judicial autopsy was ordered by the prosecutor due to an alleged medical malpractice. The autopsy confirmed the cause of death being pneumonia, but also revealed an occult restrictive cardiomyopathy with a thick and firm myocardium. Viscera samples were then collected for microscopic examination. Histopathologic analysis showed diffuse amyloid deposits in the myocardium, especially in the perivascular and subendocardial spaces. Amyloid deposits were also detected in all the other organs, except for the brain. Furthermore, immunohistochemistry for light chains was performed on the heart tissue sample, resulting to be positive. In the case presented herein, autopsy and histopathologic examination were crucial to diagnose an occult systemic amyloidosis (AL-type). In fact, it has been observed that the rarity of systematic amyloidosis and its unusual clinical onset were at first mistakenly perceived as a medical malpractice due to a technical error within the catheter ablation for atrial fibrillation. As a consequence, upon discussing the clinical and medicolegal implications concerning the case, the focus was placed on the undiagnosed systemic amyloidosis and on the causality between surgical procedure and the patient's death.